Determinants of droughts and its impact on sectoral output growth and income inequality in African countries - Bashir, Ahmad Bugaje
Droughts are natural hazards that result from reduction in rainfall water and its storage capacity which adversely affects agricultural sector and have a potential spillover effect on other economic activities. Africa has the highest occurrences of this phenomena and the second highest number of people affected within the 20th century. The region has the least natural and artificial surface storage capacity relative to other regions in the world and the countries in the region heavily depend on agricultural sector for employment opportunities and uses rainfall water as input of production in farming activities. The economic and social implications of these events in the region will increase due to climate change and vulnerability of agricultural sector. Global warming will increase climatological natural hazards like droughts around the world. Although, the continent lags behind all other regions of the world in terms of total CO2 emission from fossil fuel and per capita CO2 emissions, the continent has experienced an upsurge in the number of climatic extreme events. This calls for concern and research into the area to understand the economic implications of these events on the key sectors of the region. Drought as an example of climatic extreme event is likely to increase the disparity of income between different countries because of the likelihood of affecting the income of households in some particular sectors relative to others. In this study, drought has been measured as a percentage of normal precipitation, meaning when the calculated value of percentage of normal precipitation is lower than the threshold of 100%, there is an existence of drought and when the percentage of normal precipitation is equal or higher than the threshold of 100%, there is no existence of drought. The general objective of the study is to examine the determinant of droughts and its impact on sectoral output growth and income inequality in African countries. Objective one specifically investigates the impact of droughts on sectoral output growth for the period 1980 to 2014, for 44 African countries. The impact of droughts on income inequality and the determinants of drought fatalities in the region were investigated in objectives two and three respectively using a dataset from 2006 to 2014 for 42 and 35 African countries respectively. The preferred technique used was Generalized Method of Moments (GMM) to estimate the models of all the three objectives of the study. However, two-step system GMM estimator was used for making inferences in the study. Diagnostics and robustness checks were conducted for all the models to ensure reliability and efficiency of the estimates. The estimated results of the model in objective one revealed that droughts significantly reduce agricultural, manufacturing, mining and utility sectors’ output growth. However, drought does not affect the construction sectoral output growth. This means the former sectors are impacted by drought, while the latter sector is immune to this phenomenon. Results in objective two showed that droughts significantly increase income inequality, thus, confirms the assertion that drought increases the disparity of income between different groups and countries in Africa and dependency on agriculture sector positively related to income inequality. Lastly, results for objective three result showed that government size reduces drought fatality while dependency on agriculture activities and the low level of financial development increases drought fatalities. The general findings of the study suggest that droughts disproportionately affect different economic sectors. The results also suggest that over dependency on agricultural activities had hindered the structural transformation of the sector and policymakers needs to design programmes to fast track agricultural transformation. The general policy recommendation of the study is that African governments should focus on agricultural transformation policies to mitigate the dependency on agricultural sector and further diversify its economic structure from agricultural activities. In the short run, adaptive capacity measures should be in place to mitigate the impact of these phenomena. Policy makers should build more reservoirs and irrigation systems to increase water storage capacity for agricultural activities and disseminate information on the expected timing of rainfall to farmers by mobile phones to optimize the planting and yield of crops.